CINV: still troubling patients after all these years - Aapro, Matti (Support Care Cancer, 2018)
Chemotherapy-induced nausea and vomiting (CINV) is one of the most feared side effects experienced by patients with cancer. The precise physiologic mechanisms responsible for acute and delayed CINV continue to be elucidated and have provided an opportunity to develop antiemetic therapies targeting these pathways. The emergence of receptor antagonists targeting serotonin and neurokinin-1 have revolutionized the prevention of CINV, significantly reducing the impact of this side effect and improving patient quality of life. However, several areas of unmet need remain, including adequate prevention of nausea, rather than just vomiting, in patients receiving chemotherapy for cancer. Prevention of delayed CINV and anticipatory CINV, as well as management of breakthrough CINV, also continues to challenge patients and clinicians. Ongoing research continues to address these areas to improve antiemetic therapies and guidelines.